Interaction Profile of Problem Solving and Logical Thinking in Teaching Materials for Inheritance of Traits in Schools - Baety Nur Hanifah; Sutarno Sutarno; Sri Widoretno (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
Problem solving and logical thinking are essential 21st-century skills that are highly relevant to science learning, particularly in biology. The purpose of this study is to present the interaction profile between problem solving and logical thinking in teaching materials for the topic of inheritance of traits in schools. This research employed a descriptive qualitative method with indicator reduction. A total of 66 indicators were developed based on problem-solving aspects—Identify the problem; Define and represent the problem; Explore possible strategies; Act on the strategies; and Look back and evaluate the effects of your activities—and logical-thinking aspects, namely proportional reasoning, controlling variables, probabilistic reasoning, correlational reasoning, and combinatorial reasoning. The findings show that the teaching materials tend to emphasize the IPPR aspect (Identify – Proportional Reasoning) with an average of 4.77%, while the APBR aspect (Act – Probabilistic Reasoning) is less accommodated, with an average of 0.53%. Based on these results, the interaction profile of problem-solving and logical-thinking aspects in inheritance of traits materials in schools is presented unevenly and requires improvement. Therefore, further research is needed to develop and test problem-solving- and logical-thinking-based teaching materials through a classroom experimental approach to measure their impact on student learning outcomes. The findings of this study contribute to the field by providing an empirical basis for curriculum developers, textbook authors, and educators to design teaching materials that integrate higher-order thinking skills more evenly and effectively.